ISOLATION OF ANTIBACTERIAL PROTEIN/PEPTIDE FROM FICUS GLOMERATA LEAF - Thapliyal, Manisha; Bisht, Anjali; Singh, Ajeet (International Journal of Current Pharmaceutical Research, 2016)
Objective: To isolate the antibacterial proteins/peptides from Ficus glomerata leaf. Methods: Present study was designed to investigate antibacterial activity of proteins/peptides isolated from Ficus glomerata leaf. The isolated proteins/peptides were further checked for antibacterial activity against, Pseudomonas aeruginosa, Bacillus subtilis, Escherichia coli and Salmonella entrica bacterial pathogens. Results: The results indicates that a 35kDa of protein were identified and exhibit good antibacterial activity against bacterial pathogen among all strains, Salmonella entrica and Pseudomonas aeruginosa exhibit good results with a clear zone of inhibition. Conclusion: Ficus glomerata is popular for its medicinal properties against therapeutic potential. In the present study a novel protein with broad spectrum antibacterial activity. Microbes cause severe damage to plants which results in a large economic loss so; this protein can be use as an active agent in agriculture for plant protection and also in the development of novel therapeutic agents.